UPAYA PENINGKATAN PRODUKTIVITAS UMKM PEMBUATAN KERUPUK BU TUTIK MENGGUNAKAN METODE OBJECTIVE MATRIX (OMAX) - Saputra, Maulana Ari Eka; Satoto, Handy Febri (Universitas Majalengka, 2024)
Abstract Bu Tutik's cracker-making MSME is one of the cracker-making businesses located in Sidoarjo. This MSME is a business that operates in the manufacture of crackers. The crackers produced are like samiler crackers and puli crackers. This MSME is capable of producing up to 150 kg per month, where the production process still uses manual and simple methods. None of the processes in this MSME use machines for the production process. Productivity measurement is carried out using the OMAX (Objective Matrix) method. Next, analysis is carried out using the FTA (Fault Tree Analysis) method to obtain efforts to increase productivity.